Global Transmission of Interest Rates : Monetary Independence and the Currency Regime - Frankel, Jeffrey (World Bank, Washington, DC, 2014)
The authors empirically study the sensitivity of local interest rates to international interest rates and how that sensitivity is affected by a country's choice of exchange rate regime. To establish the empirical regularities, they use a reduced-form empirical approach to compute both panel and single-country estimates of interest rate sensitivity for a large sample of developing and industrial economies between 1970 and 1999. When using the full sample, they find that: 1) Interest rates are typically lower in economies with fixed exchange rates than in those with flexible exchange rates. 2) More rigid currency regimes tend to exhibit higher transmission than more flexible regimes. In many cases in the 1990s, however, the authors cannot reject full transmission (a slope coefficient equal to 1), even for several countries with floating regimes. The data suggest an upward time trend in the degree to which domestic interest rates are sensitive to international capital movements and developing economies' increased financial integration with the rest of the world. As a result, country-specific estimates for the 1990s reveal few cases of less-than-full transmission of international interest rates to domestic rates, regardless of the currency regime. Country-specific results suggest that only large industrial countries can (or choose to) benefit from independent monetary policy. During the 1990s, interest rates in European countries were fully sensitive to German interest rates but insensitive to U.S. interest rates.